Study on the Cross-cultural Adaptation and Academic Adaptation of South African Students - Xin Wang, (Design Engineering, 2020)
Based on the questionnaire survey of South African students studying in Zhengzhou Railway Vocational and Technical College, this paper comprehensively understands the cross-cultural adaptation and academic adaptation situation of the group from four dimensions: living environment, social interaction, campus service and academic adaptation. The results show that the average difficulty coefficient in social interaction dimension is the highest, followed by campus service and living environment adaptation, while the corresponding score of academic adaptation dimension is the lowest. In view of this, appropriate improvement strategies and suggestions are put forward to improve the cross-cultural adaptability of the students and the internationalization level of the school.